The Basic WIOD CGE Model: A computable general equilibrium model based on the World Input-Output Database - Simon Koesler; Frank Pothen (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
This report presents the Basic WIOD CGE model. The model represents the first implementation of the World Input-Output Database (WIOD) into the CGE framework and is tailored to provide a maximum fit with WIOD data. The model is specifically designed such that it can serve as the basis for research in fields like environmental, climate and trade policy. It incorporates key features of WIOD such as bilateral and bisectoral trade ows, satellite accounts for energy consumption, greenhouse gas as well as other emissions to air on a sectoral level. As all WIOD data is available in the form of a consistent time series ranging from 1995 to 2009, the model can be calibrated to any year within this time period. The model relies on substitution elasticities which are consistently estimated from the same dataset the model itself is calibrated to. Moreover, the data preparation facilities and model are designed deliberately as exible as possible in order to allow researchers to use them as a basis for various applications. This enables researchers to secure the numerous advantages of the WIOD dataset when using CGE models for future research.
urn:nbn:de:bsz:180-madoc-432356
Keywords: C67; C68; E01; 330; Computable General Equilibrium Models (CGE); Input-Output; World Input Output Database (WIOD)